Shirkah In Sharia Financial Institutions - Anisa Kamila Sari; Fiska Ummyza; Aidil Alfin (PT. AKSARA AKADEMIA INDONESIA, 2026)
Syirkah is a condition where the rights to a business are jointly owned by two or more people. With the existence of syirkah in Islamic financial institutions, it is hoped that it can create opportunities for cooperation between two or more people for the progress of joint businesses. This article aims to examine the concept and legal basis of syirkah, the pillars and conditions of syirkah, the various types of syirkah, Syirkah Mutanaqishah and Syirkah Muntahiyah bit Tamli, the MUI-DSN Fatwa on all kinds of syirkah, how syirkah is applied in Islamic Banks and LKS, how Revenue Sharing and Profit Sharing (DSN MUI Fatwa No. 15) and how to cancel syirkah. This study uses a library study method by analyzing various scientific literature and relevant educational policies. By using a research method in the form of a library research, where data is obtained from various book sources in the form of journals, documents, and policies on the implementation of syirkah in financial institutions. The results of the study show how the concept of syirkah in Islamic financial institutions and explain the application of syirkah in Islamic Banks and LKS